2005
DOI: 10.1186/bcr1340
|View full text |Cite
|
Sign up to set email alerts
|

The progestational and androgenic properties of medroxyprogesterone acetate: gene regulatory overlap with dihydrotestosterone in breast cancer cells

Abstract: Introduction Medroxyprogesterone acetate (MPA), the major progestin used for oral contraception and hormone replacement therapy, has been implicated in increased breast cancer risk. Is this risk due to its progestational or androgenic properties? To address this, we assessed the transcriptional effects of MPA as compared with those of progesterone and dihydrotestosterone (DHT) in human breast cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
55
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 72 publications
3
55
0
3
Order By: Relevance
“…MPA has a longer half-life than progesterone and can be administrated orally (Ghatge et al, 2005). The oral bioavailability of MPA was low, which was estimated to be 5 to 15% (Fotherby, 1996).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…MPA has a longer half-life than progesterone and can be administrated orally (Ghatge et al, 2005). The oral bioavailability of MPA was low, which was estimated to be 5 to 15% (Fotherby, 1996).…”
mentioning
confidence: 99%
“…Researches from Women's Health Initiative Trial indicated that the addition of MPA to conjugated equine estrogens significantly increased the risk of breast cancer (Rossouw et al, 2002;Chlebowski et al, 2003) in HRT. Prescriptions for MPA declined dramatically (Hersh et al, 2004;Wood et al, 2007) thereafter, and the reasons for increased breast cancer risk were under intense investigation (Ghatge et al, 2005;Wood et al, 2007;Otto et al, 2008). A recent study suggested that MPA underwent metabolic activation to reactive species that were genotoxic (Siddique et al, 2006).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1) is used extensively in conception and hormone replacement therapy. [1][2][3] However, due to its extensive metabolism, MPA usually has low bioavailability. Many side effects 4) are considered to be consequences of the generation of reactive metabolites from MPA.…”
mentioning
confidence: 99%